Deeper insight into thermal conductivity, size, sedimentation, band gap, and moisture effect of nanoparticles on thermo-dielectric performance of nanofluids - Farade, Rizwan A.; Mansour, Diaa-Eldin A.; Abdul Wahab, Noor Izzri; Ariffin, Mohd Khairol Anuar; Emara, Rana F.; Emara, Manal M.; El-Nemr, Mohamed K.; Rajamony, Reji Kumar (Elsevier, 2025)
Dielectric nanofluids are recognized for their ability to improve the thermal and dielectric characteristics of power equipment. Although significant research has been conducted on dielectric nanofluids, there has been limited focus on identifying the factors that influence the thermo-dielectric properties by thoroughly considering various nanoparticle-related factors. This work is important as it fills these gaps by supporting the assertion. This work aims to investigate the impact of nanoparticle thermal conductivity, size, sedimentation, bandgap, and moisture affinity to identify the factor affecting obtained nanofluid properties. Nanoparticles of Al2O3, TiO2, and SiO2, characterized by varying thermal conductivities, sizes, band gaps, and moisture affinities, are integrated into mineral oil using a two-step method. The thermo-dielectric properties encompass the heat transfer coefficient (HTC), breakdown voltage (BDV), dielectric constant, and tan δ, along with HTC at various thermal power levels, ultraviolet-visible spectroscopy (UV–Vis), dynamic light scattering (DLS), viscosity, and shear stress. The moisture effect elucidates the BDV and HTC, while the bandgap effect clarifies the dielectric constant and tan δ exhibited by nanofluids, highlighting the complex behaviour of dielectric nanofluids. The findings enhance understanding of the complex behaviour of dielectric nanofluids by pinpointing critical influencing factors. Rheological measurements of superior nanofluid (i.e., SiO2) demonstrated Newtonian behaviour, facilitating efficient operation and practical applicability.